The Influence of Audit Quality on Profit Quality in Sharia Banks Listed on the Indonesia Stock Exchange - Rifqi Badriansyah Wijaya (MEC-J (Management and Economics Journal), 2023)
A healthy company will have good earnings quality, and an independent public accountant will give a good value to the company's earnings quality. This study aims to determine the effect of audit quality on earnings quality in sharia banks. This study uses explanatory research based on hypothesis testing. The data source is secondary data from sharia banking companies listed on the IDX for the 2021-2022 period and is based on quarterly financial reports. The sampling technique was purposive sampling with a total sample of 4 sharia banks. The analysis used is descriptive, simple linear regression, and hypothesis testing. The results showed that there was no significant effect between audit quality variables on earnings quality. The audit quality of sharia banking companies listed on the IDX cannot be determined from the quality of the auditors. This is indicated by the formation of sharia banking which must have reliable governance to encourage strong and effective sharia compliance so that the public image, namely the interests of stakeholders, can realize economic activities in accordance with sharia principles.